Outcome study of early onset schizophrenia - Esther, E.; Jesjeet, S.G.; Aili, H.H. (2005)
Schizophrenia is a serious mental illness that often affects young people with an enormous impact not only on the patient and family, but society as a whole. The outcome of early onset schizophrenia is often poor with one quarter to one third having bad prognosis.